Indonesia dan Filipina: Perbandingan Sistem Pemilu Legislatif Dua Negara Asia Tenggara - Achmad Surya Hadi Kusuma (CV. Era Digital Nusantara, 2023)
Indonesia and the Philippines are two countries in the Southeast Asian region that have almost the same past political history. Both of these countries were ruled by authoritarian rulers. The electoral political system at that time was made and totally controlled through all political elements. Democracy does not live and shackled to the political system run by the authorities. In order to measure the quality of a country's democracy, it can be seen from the procedures of democracy in the form of general elections. If the elections in that country are good, people's participation is also conveyed well, then it can be categorized that the country has good quality democracy. This is also a lesson for Indonesia and the Philippines to be better at holding elections and their democracy by producing legal products and forming a better electoral system than before. The electoral system from time to time continues to change according to the conditions in each country to obtain an electoral system that is beneficial to its people.